A study on farmers’ choice in integrating paddy and cattle farming as farm management practices - Widarni, N. A. A.; Kusumastuti, T. A.; Putra, A. R. S. (Diponegoro University, 2020)
The study was conducted to examine the farmers’ choice on the technology of the paddy and cattle integration farming and determine factors that affected the integrated adoption. Primary data were collected through personal interview from 198 respondents divided into three categories (‘no integration’, ‘partial integration’, and ‘full integration’) based on the farmer’s utilization of manure and crop residues at Magelang Regency, Central Java Province, Indonesia. Then, the data were analyzed by multinomial logit by using ‘no integration’ as a baseline. The results revealed that 60.6% of farmers had applied ‘full integration’, although most farmers rarely adopt both fermentation and composting technology. In conclusion, formal education, frequency of training, and farming experience were found significant in affecting the integration of paddy and cattle farming practice.